Kajian Agribisnis Komoditas Unggulan Tanaman Pangan di Kabupaten Lima Puluh Kota - Marlinda, Barirah; Lubis, Iskandar; Sitorus, Santun R.P (P4W IPB, 2023)
Superior agricultural commodities, especially food crops, are one of the development potency in Lima Puluh Kota Regency, West Sumatra Province. Therefore, it is necessary to study the superior commodities by considering agribusiness systems from upstream to downstream in order to increase regional competitiveness and people's welfare. This study was conducted to identify superior food crops and examine the agribusiness system of superior food crops in Lima Puluh Kota Regency. Based on the analysis of superior commodities using Location Quotient (LQ) and Shift Share Analysis (SSA), superior food crop commodities are rice, corn, peanut, and cassava. These superior commodities are spread over 8 districts, namely Mungka, Payakumbuh, Harau (rice), Guguak, Luak, Lareh Sago Halaban (corn), Suliki (peanuts), and Akabiluru (cassava). The analysis of the agribusiness system describes the conditions of each agribusiness sub-system of the superior food crop commodities starting from the upstream (on-farm) downstream (off-farm). The agribusiness system for superior food crop commodities in Lima Puluh Kota Regency has not run well, integrated and synergistic, especially in the downstream agribusiness subsystem.